Peningkatan Pengetahuan Ibu PAUD tentang Gizi Seimbang dan Pentingnya Konsumsi Sayur dan Buah di Desa Sukanagalih, Cianjur - Lina Agestika; Mia Srimiati; Renan Prasta Jenie (Jurnal Abdimas Kesehatan (JAK), 2022)
Cianjur is potential province for vegetables and fruit commodities compared to other Java provinces. Despite abundant crop production, stunting prevalence among under-five is high, while the dietary diversity score was low. To prevent and overcome nutritional problems, a strategy is required to improve dietary diversity consumption patterns. The participant in this community service activity in Sukanagalih Village, Cianjur mothers, and students of PAUD. Participants are expected to gain more knowledge about the benefits of fruit and vegetable consumption and balanced diet. Further, it would enhance their motivation to utilize the home yard to grow vegetables and fruit. The activities are nutrition education in the classroom about the nutritional value in my plate, guidelines for balanced diet, and the adequacy of vegetables and fruit, continue with seed planting activities, and games. The number of participants in this activity is 22 pairs of mothers and children. Data analysis on nutrition knowledge scores of mothers was using the Wilcoxon signed rank test. The results showed that 59% of mothers experienced increased nutrition knowledge. The median mother's knowledge score on the pre-test was 64.3 ± 15.8 and the post-test was 71.4 ± 9.9 with a p-value > 0.05. This shows that nutrition education for short duration is not sufficient to increase the mother's knowledge. The enthusiasm of mothers and students in participating in counseling and planting seeds activities is very high. However, longer duration and frequency of activities and the use of local languages are necessary for more significant result.